Analisa Kekuatan Rem Depan Motor Yamaha Jupiter MX 135cc Tahun 2013 - Ismail Ismail; Jojo Sumarjo; Rizal Hanifi (Peneliti.net, 2023)
Brakes in general are a system that works to slow down or stop rotation. The principle of the brake is to convert the energy of motion into heat energy. The braking effect is obtained from the friction caused between two objects. The method in the calculation is by direct observation to find data in the form of specifications on the front brake components of yamaha jupiter mx 135cc 2013 motorcycle, then the calculation process is carried out to determine the type of force on the fornt brake such as hand force (, piston force (, piston compression force on the canvas (F), braking force (. Based on the results of the study, it is known that hand force ( = 235 Kgf, piston force ( = 493,5 Kgf, piston comression force on the canvas (F) = 3454,56 Kgf (2 canvas), braking force ( = 82,18 Kgf.